Validation of biplane high‐speed fluoroscopy combined with two different noninvasive tracking methodologies for measuring in vivo distal limb kinematics of the horse. (4th September 2017) - Geiger, S. M.; Reich, E.; Böttcher, P.; Grund, S.; Hagen, J.
Summary: Reason for performing study: Biplane high‐speed fluoroscopy is a new method for gait analysis of the equine distal extremity. This is the first study validating the noninvasive tracking possibilities (Autoscoping and Scientific Rotoscoping) taking equine anatomy into account. Objectives: To determine the resolution with which Autoscoping and Scientific Rotoscoping depict motion of the equine phalanges in comparison to the invasive gold standard marker‐based registration. Study design: Comparative ex vivo study. Methods: In 5 distal extremities of slaughtered ponies, 3 or 4 tantalum beads with 1 mm diameter were implanted in each of the proximal, middle and distal phalangeal bones. Three‐dimensional models of the bones were reconstructed using computed tomographic data (120 kV, 50 mA, slice thickness 1 mm, increment 0.5). The beads were digitally removed from the bone models. Biplane fluoroscopic videos were taken at 69.5 ± 3.5 kV, 102.5 ± 22.5 mA, 500 frames/s and 0.5 ms shutter speed. The 5 specimens were moved in the trial field of the biplane fluoroscopic setup in a step‐like motion (simulation of landing, main stance phase, lift‐off). Marker‐based registration, Autoscoping and Scientific Rotoscoping were carried out. For statistical analysis agreement was computed as percentiles, mean and s.d. Results: The medians of Scientific Rotoscoping ranged from 0.16 to 0.66 mm in translations and 0.43 to 2.78° in rotations, while values for Autoscoping were 0.13–0.70 mm and 0.28–2.39° respectively. With 2 exceptions, all differences between methods were statistically significant. Scientific Rotoscoping is more time efficient than Autoscoping and results in smaller maximum errors. Main limitations: The experimental set‐up was specifically designed to accommodate in vivo requirements. Autoscoping was not manually corrected but rather expected to work automatically. Conclusions: It is possible to noninvasively apply both Autoscoping and Scientific Rotoscoping for gait analysis of the equine phalanges with high precision. The summary is available in Chinese ‐ see supporting information.